Music Computer Education Concept for Teachers: Raising the Problem (International journal of recent technology and engineering, 2019)
The beginning of the 21th century was marked by the introduction of computer and communication technologies in all spheres of human activity. Global changes have occurred in the way information is transmitted and presented. Digital technology has penetrated into music and education. The achievements of sound recording, the technology of creating musical compositions combined with the new mass media possibilities have defined the previously non-existent areas of development and distribution of music, and require such knowledge that musicians who have received a classic music education do not have.The article describes the basic, which is devoted to development of actual theoretical and practical basis of raising knowledge of students in music department with usage of music computer technologies